Over a million students use our free study notes to help them with their homework
f(x) = 2sin2(2x)Therefore, using the chain rule: f'(x)=2 x 2cos(2x) x 2sin(2x)(The 2 at the front arises from the constant 2, at the start of f(x), the 2cos(2x) comes from differentiating sinAnswered by Sam H. • Maths tutor4205 Views
To find inverse functions we swap the variables of the function we are taking the inverse of. let y=1+2sin(3x)so now, x=1+2sin(3y)Aiming to make y the subject, x-1= 2sin(3y)Therefore, (x-1)/2=sin(3y), ...
By product rule:u = 4sin(x) v = cos(3x)du/dx = 4cos(x) dv/dx = -3sin(3x)dy/dx = u (dv/dx) + v (du/dx)dy/dx = 4sin(x) * -3sin(3x) + cos(3x) * 4cos(x)dy/dx = -12sin(x)sin(3x) + 4cos(x)cos(3x)Evaluate at x =...
We can explain this by taking a simple power equation such as 23 = 8 and setting each number as an unknown variable. For instance 23 = x is solved by cubing 2, x3 = 8 is s...
←
258
259
260
261
262
→
Internet Safety
Payment Security
Cyber
Essentials